The language-in-education policy : opportunities and challenges of implementation in a suburban school. - Magwa, Eunice Ntombizodwa (My University, 2013)
This study is a qualitative evaluation of how one state school interprets and makes a decision on the language medium to use as guided by the Language in Education Policy [LiEP] that advocates multilingualism in schools. The study asks how the LiEP ideal informs the language policy in the school, and establishes reasons parents give for choosing English as medium of instruction to be used in classrooms. Following Parlett and Hamilton‟s (1976) evaluation as illumination framework, this study outlines the language medium ideal expressed in LiEP and describes the actual Language Policy of the School in practice and how it accords with LiEP in guiding the medium of instruction. Data collection methods in this report included document analysis, classroom observations, interviews and questionnaires. The key findings from the data illuminate; parents of the learners in the school view the national language policy in a positive light that it is inclusive despite the challenges it presents to implementation. The findings reflected the decision makers‟ endeavour to strengthen their case that by choosing English as medium of instruction is not to contravene the policy, but a democratic right to benefit their children. Findings in the report suggest that the national language policy in South Africa is regarded a valuable document to guide the selection on the medium of instruction in schools, but raises issues that need to be addressed to make it play a more effective role in educational contexts.
Keywords: Education, Bilingual--South Africa.; Multilingualism--South Africa.; Language and education--South Africa.; Language policy--South Africa.